PEMBELAJARAN LABORATORIUM SOSIAL PENDIDIKAN AGAMA ISLAM BERBASIS MODERASI BERAGAMA - Eka Putra Romadona; Amar Ma'ruf; Imam Syafi'i; Suparto Suparto (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
Islamic education is the accumulation of knowledge originating from the Al-Qur'an and As-Sunnah, taught, fostered, and instructed to mankind as students through the application of methods and methods designed to develop students with Muslim personalities. In Islamic education, an increase in student moderation coincides with an increase in character. So it is felt that there is a need for a form of design to be able to help facilitate Islamic religious education to achieve the desired goals. The literature study was used in this research to obtain data about Islamic religious moderation-based social laboratory learning. The data obtained is then analyzed by following a flow that includes data simplification, data visualization, and drawing conclusions. This research seeks to develop a Religious Moderation-based PAI Social Laboratory Learning design. This study tries to describe the design of PAI learning based on the value of religious moderation. The results of this study are a design of PAI learning which is designed through several stages, including analysis to evaluation, and revision. This research itself has contributed to the discussion of Islamic religious education in Indonesia which focuses on the themes of religious moderation.